STUDENT PROBLEMS IN LEARNING ISLAMIC RELIGIOUS EDUCATION IN MAN CURUP: ANALYSIS OF THE TYPES, NUMBERS, AND TEACHER'S EFFORTS IN ALLEVIATE IT - Sutarto Sutarto (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2020)
The present study aimed to reveal the types and numbers of problems as well as teachers’ coping efforts to help students solve their problems in Islamic education learning. This study applied a mixed method deploying a transformative congruent strategy. The population referred to 102 social science students of grade XI at MAN Curup. They were all involved as the samples at once. Subsequently, 4 Islamic education teachers and 3 supervising teachers were incorporated as the informants. The techniques of data collection deployed questionnaires in the form of a problem disclosure instrument called AUM PTSDL and structured interviews. This study uncovered that the types of learning problems experienced by students extended to those associated with prerequisites for the mastery of learning materials (P), learning skills (T), learning facilities (S), personality (D), and learning environments and socio-emotional aspects (L). The average number of problems per student was 50.67. The most problems experienced by students were those of learning skills (T) with the average of 23.6 per student. Subsequently, the least problems were those of learning facilities (S) with the average of 3.7 per student. The coping efforts the teachers made were by means of remedial activities and the provision of counseling guidance services by supervising teachers. Keywords: Types of learning problems; the number of learning problems; Islamic religious educationAbstrak Penelitian ini bertujuan untuk mengungkapkan jenis, jumlah dan upaya yang dilakukan oleh guru untuk mengentaskan masalah belejar siswa dalam pembelajaran Pendidikan Islam.  Penelitian ini menggunakan mtode mixed methods dengan strategi transformatif konkuren. Populasi penelitian ini adalah siswa kelas XI Jurusan IPS kelas XI MAN Curup yang berjumlah 102 orang dan sekali gus menjadi sampel penelitian. Informen penelitian terdiri dari guru yang mengajar Pendidikan Islam yang berjumlah 4 orang dan guru pembimbing berjumlah 3 orang. Teknik pengumpulan data menggunakan kuisoner berupa Alat Ungkap Masalah PTSDL dan wawancara terstruktur. Hasil penelitian menunjukkan bahwa jenis masalah belajar yang dialami oleh siswa terdiri dari masalah berkaitan dengan Prasyarat Penguasaan Materi Pelajaran (P), Keterampilan Belajar (T), Sarana Belajar (S), Diri Pribadi (D), dan lingkungan Belajar dan Sosio Emosional (L). Jumlah masalah belajar yang dialami siswa rata-rata sebesar 50.67. Masalah yang paling banyak dialami oleh siswa adalah aspek keterampilan belajar (T) dengan rata-rata sebesar 23.6 dan terendah pada aspek sarana belajar (S) dengan rata-rata 3.7 per siswa. Upaya yang dilakukan oleh guru untuk membantu mengentaskan masalah belajar siswa adalah melalui kegiatan remedial dan pemberian layanan bimbingan konseling oleh guru pembimbing. Kata Kunci : Jenis masalah belajar; jumlah masalah belajar; pendidikan agama Islam